2007
DOI: 10.3354/dao074085
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of a Thai strain of white spot syndrome virus (WSSV) in juvenile, specific pathogen-free Litopenaeus vannamei

Abstract: White spot syndrome virus (WSSV) causes disease and mortality in cultured and wild shrimp. A standardized WSSV oral inoculation procedure was used in specific pathogen-free (SPF) Litopenaeus vannamei (also called Penaeus vannamei) to determine the primary sites of replication (portal of entry), to analyze the viral spread and to propose the cause of death. Shrimp were inoculated orally with a low (10 1.5 shrimp infectious dose 50% endpoint [SID 50 ]) or a high (10 4 SID 50 ) dose. Per dose, 6 shrimp were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…Therefore, it could be reasonably inferred that collapse of the supportive connective tissue was responsible for the profound pathological changes of hepatopancreatic tubules; nevertheless, they themselves were not susceptible to the virus. This result agrees with the studies done in P. monodon Wang et al, 1999) and L. vannamei (Escobedo-Bonilla et al, 2007) which revealed virus replication in the myoepithelial cells of the hepatopancreatic sheath and cells of the connective tissues but not in the hepatopancreatic tubular epithelial cells.…”
Section: Hepatopancreassupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, it could be reasonably inferred that collapse of the supportive connective tissue was responsible for the profound pathological changes of hepatopancreatic tubules; nevertheless, they themselves were not susceptible to the virus. This result agrees with the studies done in P. monodon Wang et al, 1999) and L. vannamei (Escobedo-Bonilla et al, 2007) which revealed virus replication in the myoepithelial cells of the hepatopancreatic sheath and cells of the connective tissues but not in the hepatopancreatic tubular epithelial cells.…”
Section: Hepatopancreassupporting
confidence: 93%
“…Virus replication at different stages of morphogenesis was observed in this tissue even when animals were moribund. Previous studies showed that connective tissue of the nervous system were alone infected by WSV (Karunasagar et al, 1997;Sudha et al, 1998;Wang et al, 1999;Escobedo-Bonilla et al, 2007). It is therefore concluded that both neurosecretory and connective tissue of the nervous system are equally susceptible to WSV infection.…”
Section: Nervous System 331 Nervementioning
confidence: 92%
See 3 more Smart Citations